2020
DOI: 10.3390/ijms21093321
|View full text |Cite
|
Sign up to set email alerts
|

Niacin Alleviates Dairy Cow Mastitis by Regulating the GPR109A/AMPK/NRF2 Signaling Pathway

Abstract: Mastitis is one of three bovine diseases recognized as a cause of substantial economic losses every year throughout the world. Niacin is an important feed additive that is used extensively for dairy cow nutrition. However, the mechanism by which niacin acts on mastitis is not clear. The aim of this study is to investigate the mechanism of niacin in alleviating the inflammatory response of mammary epithelial cells and in anti-mastitis. Mammary glands, milk, and blood samples were collected from mastitis cows no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Work with non-ruminants confirmed that NFE2L2 activates autophagy through the control of LAMP2A transcription, which alleviates oxidative stress by inhibiting accumulation of oxidized protein aggregates [ 17 ]. Interestingly, the regulation of autophagy via NFE2L2 also was confirmed in primary bovine mammary epithelial cells [ 18 ]. Thus, NFE2L2-mediated autophagy might play a protective role against oxidative stress in bovine mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Work with non-ruminants confirmed that NFE2L2 activates autophagy through the control of LAMP2A transcription, which alleviates oxidative stress by inhibiting accumulation of oxidized protein aggregates [ 17 ]. Interestingly, the regulation of autophagy via NFE2L2 also was confirmed in primary bovine mammary epithelial cells [ 18 ]. Thus, NFE2L2-mediated autophagy might play a protective role against oxidative stress in bovine mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhao et al (58) found that lncRNA UCA1 could accelerate cell viability, block apoptosis and function as competitive endogenous RNA (ceRNA) to target TLR4 by sponging miR-499b-5p, thereby alleviating the LPS-challenged cell damage. Based on above results, it was speculated that these DElncRNAs are likely involved in regulating the process of bovine mastitis via their immune-related target genes (7,(59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, BMECs, as one of the main cells of mammary tissue, are not only important immune cells, but also a major cell population for lactation in cows ( 28 , 35 ). When mastitis occurs in cows, mastitis is well known to seriously affect milk production and quality ( 11 , 19 , 34 ). Yusaku Tsugami et al.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear transcription factor Nrf-2 is considered an important regulator of cellular homeostasis; and is capable of activating the expression of a variety of cytoprotective genes ( 46 ). AMPK, as a kinase working upstream of Nrf-2, has an important role in the regulation of Nrf-2 ( 19 ). Under normal conditions, Nrf-2 exists in free form, in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation